MUSIC IN THE ACADEMIC LIBRARY OF TOMORROW. - Walker, Diane Parr (Notes, 2003)
Examines issues that are considered in the planning for the future of academic libraries and discusses music reflected in such libraries in the U.S. Discussion on the changing nature of academic music collections and their audience; Instances which show the influence of music in contemporary life; Advantages of digitization to libraries.